Antibody responses to cancer antigens identify patients with a poor prognosis among HPV-positive and HPV-negative head and neck squamous cell carcinoma patients - Laban, Simon Andreas; Gangkofner-Strauss, Dominik Stefan; Holzinger, Dana; Schroeder, Lea; Eichmüller, Stefan B.; Zörnig, Inka; Jäger, Dirk; Wichmann, Gunnar; Dietz, Andreas; Broglie, Martina A.; Herold-Mende, Christel; Dyckhoff, Gerhard; et al. (Clinical cancer research, 2019)
The identification of high-risk patients within human papillomavirus (HPV)-positive and -negative head and neck squamous cell carcinoma (HNSCC) is needed for improved treatment and surveillance strategies. In this study, we set out to discover antibody responses (AR) with prognostic impact in HNSCC stratified by HPV status.